Complete 3-Qubit Grover search on a programmable quantum computer. Issue 1 (December 2017) - Figgatt, C.; Maslov, D.; Landsman, K.; Linke, N.; Debnath, S.; Monroe, C.
Abstract The Grover quantum search algorithm is a hallmark application of a quantum computer with a well-known speedup over classical searches of an unsorted database. Here, we report results for a complete three-qubit Grover search algorithm using the scalable quantum computing technology of trapped atomic ions, with better-than-classical performance. Two methods of state marking are used for the oracles: a phase-flip method employed by other experimental demonstrations, and a Boolean method requiring an ancilla qubit that is directly equivalent to the state marking scheme required to perform a classical search. We also report the deterministic implementation of a Toffoli-4 gate, which is used along with Toffoli-3 gates to construct the algorithms; these gates have process fidelities of 70.5% and 89.6%, respectively. Grover's algorithm provides a quantum speedup when searching through an unsorted database. Here, the authors perform it on 3 qubits using trapped ions, demonstrating two methods for marking the correct result in the algorithm's oracle and providing data for searches yielding 1 or 2 solutions.